Are lead-free piezoelectrics more environmentally friendly?. (16th February 2017) - Ibn-Mohammed, T.; Koh, S. C. L.; Reaney, I. M.; Sinclair, D. C.; Mustapha, K. B.; Acquaye, A.; Wang, D.
Abstract: Abstract : Considered as a less hazardous piezoelectric material, potassium sodium niobate (KNN) has been in the fore of the search for replacement of lead (Pb) zirconate titanate for piezoelectrics applications. Here, we challenge the environmental credentials of KNN due to the presence of ~60 wt% Nb2 O5, a substance much less toxic to humans than Pb oxide, but whose mining and extraction cause significant environmental damage.